A new species of Campyloneura (Hemiptera: Heteroptera: Miridae) from Cameroon with a review of the genus - Konstantinov, Fedor V. (Zootaxa, 2021)
A second species of the previously monotypic plant bug genus Campyloneura, C. joceliae sp. nov. is described based on specimens from Nkolbisson, Cameroon. A key, differential diagnoses, digital habitus images, illustrations of male and female genitalic structures, and scanning micrographs of diagnostic morphological structures are provided for the new species and C. virgula (Herrich-Schaeffer, 1835).